2013
DOI: 10.1155/2013/502968
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Anemia among Children 6–59 Months Old in Haiti

Abstract: Anemia has serious consequences on child growth, development, and survival. This study was conducted in Fond des Blancs and Villa, Haiti, to assess the prevalence of childhood anemia and its risk factors in order to inform program design. Children 6–59 months old (n = 557) were selected using a cross-sectional multistage sampling methodology. Hemoglobin was measured using the HemoCue technique. Descriptive and multivariate analyses were performed to determine prevalence and factors associated with anemia. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
70
1
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 6 publications
25
70
1
13
Order By: Relevance
“…This finding is inconsistent with a study conducted in Kenya, which revealed thatanaemia was significantly higher in male than female children (p<0.001) [5].In the current study, though there was no significant association, children aged 48 to 59 months compared to those less age 6-11 months were 61% times less likely to develop anaemia as compared to the children aged 6-11 months (AOR=0.39, p=0.061). This finding is consistent with a study conducted in Haiti where children under 24 months were 2.6 times more likely to develop anaemia as compared to the older age (OR=2.6;P<0.001) [18].Another study conducted in Brazil also reported that children aged 24-35, 36-47 and 48-59 months were 0.61, 0.49 and 0.41 times less likely to develop anaemia [17].Another study conducted in North eastern Brazil also revealed that there was a significant association between children aged (6 to 23 months) and anaemia p<0.001) [8].The dietary sources of iron are very important to keep up with the rapid rate of red blood cell synthesis, since anaemia may result if thedietary sources are inadequate [8,20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is inconsistent with a study conducted in Kenya, which revealed thatanaemia was significantly higher in male than female children (p<0.001) [5].In the current study, though there was no significant association, children aged 48 to 59 months compared to those less age 6-11 months were 61% times less likely to develop anaemia as compared to the children aged 6-11 months (AOR=0.39, p=0.061). This finding is consistent with a study conducted in Haiti where children under 24 months were 2.6 times more likely to develop anaemia as compared to the older age (OR=2.6;P<0.001) [18].Another study conducted in Brazil also reported that children aged 24-35, 36-47 and 48-59 months were 0.61, 0.49 and 0.41 times less likely to develop anaemia [17].Another study conducted in North eastern Brazil also revealed that there was a significant association between children aged (6 to 23 months) and anaemia p<0.001) [8].The dietary sources of iron are very important to keep up with the rapid rate of red blood cell synthesis, since anaemia may result if thedietary sources are inadequate [8,20].…”
Section: Discussionsupporting
confidence: 92%
“…A similar finding was reported in Uganda where 2 out of every 3 children of young mothers had anaemia [18]. Another study in Northeastern Brazil also showed that children of mothers aged less than 20 years were 1.7 times more likely to have anaemia compared to older age group (p<0.001) [8].…”
Section: Discussionsupporting
confidence: 72%
“…1 Estimates suggest that 47.4% of children under five years of age are anaemic globally. 2 The most significant contributor to the onset of anaemia is iron deficiency and World Health Organization estimates that iron deficiency anaemia affects 50 percent of women and 40 percent of children in developing countries.…”
mentioning
confidence: 99%
“…Penurunan sekresi tersebut menyebabkan stunting 8 . Hubungan stunting dan anemia ditunjukkan oleh penelitian Ayoya, et al (2013) yang menunjukkan bahwa terdapat hubungan antara kejadian stunting dengan kejadian anemia. Bahkan salah satu penelitian di Ghana menunjukkan bahwa balita stunting memiliki risiko 2 kali lebih besar terkena anemia daripada balita non stunting 9 Prevalensi balita stunting di Surabaya masih cukup tinggi yaitu 21,5% pada tahun 2014.…”
Section: Pendahuluanunclassified
“…Hubungan stunting dan anemia ditunjukkan oleh penelitian Ayoya, et al (2013) yang menunjukkan bahwa terdapat hubungan antara kejadian stunting dengan kejadian anemia. Bahkan salah satu penelitian di Ghana menunjukkan bahwa balita stunting memiliki risiko 2 kali lebih besar terkena anemia daripada balita non stunting 9 Prevalensi balita stunting di Surabaya masih cukup tinggi yaitu 21,5% pada tahun 2014. Salah satu daerah di Surabaya dengan prevalensi balita stunting yang cukup tinggi adalah Kelurahan Tambak Wedi yaitu sebesar 33% pada tahun 2016.…”
Section: Pendahuluanunclassified